2012
DOI: 10.1097/ta.0b013e318251fb34
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the need for tracheostomy in patients with cervical spinal cord injury

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 18 publications
2
59
1
1
Order By: Relevance
“…B erney et al [106] also found volume of pulmonary secretions and gas exchange to be predictive of airway management. Tracheostomy may be performed as early as day 4 following anterior cervical surgery with no increase in the incidence of wound or implant infection [118], and has been associated with fewer days on the ventilator and a shorter hospital stay in selected patients [119]. …”
Section: Respiratory Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…B erney et al [106] also found volume of pulmonary secretions and gas exchange to be predictive of airway management. Tracheostomy may be performed as early as day 4 following anterior cervical surgery with no increase in the incidence of wound or implant infection [118], and has been associated with fewer days on the ventilator and a shorter hospital stay in selected patients [119]. …”
Section: Respiratory Treatmentmentioning
confidence: 99%
“…With increased survival after high SCI, long-term ventilation is now 6–8% prevalent in the developed world [119, 138140]. It is a common assumption amongst the able-bodied that life with a high SCI would not be worth living [3]; however, research into perceived QOL in the ventilator-associated SCI group indicates that this is not the case.…”
Section: Respiratory Treatmentmentioning
confidence: 99%
“…In a retrospective study [80], early tracheostomy (<day 7) in traumatic SCI patients was associated with a shorter duration of mechanical ventilation, shorter length of ICU stay, and decreased laryngotracheal complications, but they could not demonstrate that early placement prevents the risk of ventilator-associated pneumonia or affects the mortality rate. A retrospective review of patients with cervical SCI [81] verified that tracheostomy decreased the mortality rate and pulmonary complications compared with endotracheal intubation longer than 7 days, and they demonstrated that early tracheostomy facilitates quicker extubation and shorter hospital stays. They recommend early tracheostomy if at least two of the following three factors are present: the Injury Severity Score (ISS) > 32, the patient has a complete SCI, or PaO 2 /FiO 2 ratio <300 3 days after mechanical ventilation was initiated.…”
Section: Tracheostomymentioning
confidence: 99%
“…[10][11][12] Early tracheostomy (ET) has been shown to decrease intensive care unit (ICU) length of stay, overall hospital length of stay, and facilitate weaning from MV. [13][14][15][16] As the benefits of tracheostomy appear most pronounced when performed early during hospitalization, identification of patients who are unlikely to wean from MV would permit ET.…”
mentioning
confidence: 99%